2008
DOI: 10.1016/j.ajog.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

A national study of the complications of lupus in pregnancy

Abstract: Objective-To determine the risk of rare complications during pregnancy for women with systemic lupus erythematosus (SLE).Study Design-Using the Nationwide Inpatient Sample from 2000 to 2003, we compared maternal and pregnancy complications for all pregnancy-related admissions for women with and without SLE.Results-Out of over 16.7 million admissions for childbirth over the 4 years, 13,555 were to women with SLE. Maternal mortality was 20-fold higher among women with SLE. The risks for thrombosis, infection, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
350
5
25

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(402 citation statements)
references
References 20 publications
22
350
5
25
Order By: Relevance
“…According to the literature, one third of pregnancies will result in a cesarean section, 33% will have preterm birth, and more than 20% will be complicated by preeclampsia [3,4,12,16]. Pregnancy outcome in SLE and the risks for these complications relate to lupus activity, antiphospholipid antibodies, renal status, hypertension, and medication complications [4,10,13,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, one third of pregnancies will result in a cesarean section, 33% will have preterm birth, and more than 20% will be complicated by preeclampsia [3,4,12,16]. Pregnancy outcome in SLE and the risks for these complications relate to lupus activity, antiphospholipid antibodies, renal status, hypertension, and medication complications [4,10,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these complications can be attributed to SLE treatment more than to the disease itself. Several factors are believed to influence the outcome of pregnancy, namely lupus activity, antiphospholipid antibodies, renal status, hypertension and medication complications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated individual medical comorbidities, such as pre-existing asthma, hypertension, malignancy, chronic ischaemic and congenital heart disease, chronic renal disease, systemic lupus erythematosus, hypercoagulability states, human immunodeficiency virus and diabetes mellitus, to be associated with both severe maternal morbidity and mortality, 25,153,[162][163][164][165][166][167][168] but the extent of the population risk attributable to medical comorbidities as a whole in the UK has not previously been quantified. Uptake of antenatal care was found to be poorer among women with medical comorbidities in our study population, which could increase the adverse effects associated with these conditions.…”
Section: Conclusion and Implications For Policy And Practicementioning
confidence: 99%
“…Adverse pregnancy outcomes have been reported in mothers with systemic lupus erythematosus (SLE) and their offspring 1, 2, 3. These include preeclampsia, preterm birth, stroke, and even death.…”
Section: Introductionmentioning
confidence: 99%